Control of active car suspension system based on 2PID and PSO Optimization (Texas Journal of Engineering and Technology, 2022)
Active suspension systems are essential to improve vehicle performance and ride comfort under various road vibrations. Active suspension systems proved a better option compared to a passive suspension system. It has an actuator that produces a force that reduces the turbulence caused by road interference. The suspension in this research is controlled by a 2Proportional-Integral-Derivative (PID) and optimize the gains using the Particle Swarm Optimization (PSO) method. Three forms of road disturbances are studied one is sine and step input and a single and two bumps. Simulation results demonstrated the advantage of 2PID controllers-based PSO algorithm in terms of improving the dynamic performance of the active suspension system regarding to body acceleration position and deflection and provide good tire-road contact.